Analisis Sistem Pelayanan Rekam Medis Rawat Inap di RSUP Dr. Kariadi Semarang Tahun 2016 - Dewi, Nur Fadilah; Agustina, Karmelia (UI Scholars Hub, 2017)
This research aims to describe the Analysis of Medical Record Service System in Dr. Kariadi. The method used is qualitative method, to know the clear picture about the problems studied. Data collection by observation, in-depth interviews, and documentation. The results of this study indicate that Dr. Kariadi already has written Service Operational Standard on service and Medical Record Management based on Director of Dr. Kariadi. Compliance of the medical officers in this case the doctors in charge is still less due to busy, so there are still not complete the medical record documents, there is still missing or forgotten in the filling, for example, signatures, dates, hours and complete diagnosis due to Unreadable writing. It should still be reminded by the medical recorder who served in the inpatient room, in this case is the Charge of Medical Record (PJRM). The lack of computers for PJRM, as well as the limited space for document storage are still a constraint, PJRM must wait their turn in using computers to enter data, analyze, perform coding, in the treatment room. So also where the document is still less because the medical record is still manual, and the number of patients getting more days.